CO2 field-flooding devices offer potential value for cardiopulmonary bypass procedures for CHD performed via a right-side small incision approach - Zhangke Guo; Zhimin Li; Song Bai; Feng Tong; Jia Zheng; Nan Ding; Xiaofeng Li (Journal of Cardiothoracic Surgery)
Abstract Objective This study sought to evaluate the value of a CO2 field-flooding device in cardiopulmonary bypass (CPB) surgical procedures for congenital heart disease (CHD) performed via a right-side small incision approach. Methods Between April 2022 and December 2023, 234 children with simple CHD who underwent CPB via a right-side small incision approach were separated into a control group (n = 93) without the use of a CO2 field-flooding device and a treatment group (n = 141) in which this device was added to the traditional surgical manual exhaust. Demographic, perioperative, arterial blood gas (ABG), and laboratory test data were then compared between these groups of patients. Results There was a significant difference in abnormal electrocardiogram (ECG) after aorta de-clamping during CPB, and interventions for abnormal ECG after aorta de-clamping during CPB between the control and treatment groups (17(18.3%) vs.14(9.9%), P = 0.048;12(85.7%) vs.7(50%),P = 0.013). The treatment group exhibited a lower pH (7.34 ± 0.07 vs. 7.36 ± 0.06, P = 0.039) and a higher PaCO2 (43.08 ± 7.36 vs. 38.86 ± 5.65 mmHg, P = 0.042) at the time of 30 min after initiation of CPB. A significant reduction in postoperative CK-MB was observed in treatment group (41.20 ± 17.88 vs. 56.57 ± 22.99 U/L, P = 0.002). Lower 3-day postoperative CRP levels were also observed in the treatment group relative to control (5.77 ± 0.48 vs. 9.45 ± 0.98 mg/L, P < 0.001). The S100ß concentration in the relevant patient cohort increased significantly from the time just after induction, intubation, and installation of the right central venous line to the time of admission to CCU (71.61 ± 11.83 vs. 124.04 ± 38.80, P = 0.01) and at the time of 24 h after operation (71.61 ± 11.83 vs. 101.97 ± 30.31, P = 0.01). No differences on S100β serum concentration level were found at the time of installation of the right central venous line between two groups. But there were statistically significant differences in S100β serum concentration level at the time of admission to CCU between control group and treatment group. (161.19 ± 6.62 vs. 86.89 ± 9.69 pg/ml, P = 0.01). Similar results were observed at the time of 24 h after operation. (127.62 ± 19.44 vs. 76.33 ± 10.40, P = 0.01). Conclusion These data suggest that the CO2 field-flooding device can safely be used when performing CPB surgical procedures via a right-side small incision approach to treat CHD without hypercapnia. The use of such a CO2 field-flooding device at a flow rate of 5 L/min may help protect against cardiac and nervous system damage in children undergoing CHD surgery.